The Regime of Governance and Administration in The Saudi State and The Participation of The Shahran Tribe - Al shahrani, Saeed Ali; Abdul Hamid, Faisal Ahmad Faisal; Binti Ali, Aizan (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2017)
The regime of imamate and Succession play a great role in the inception and continuity of states, especially the Royal States. Like the establishment of the Saudi Arabia State in Najd at the twelfth century Hijri, these regimes emerged because the state needed it. Despite the succession of the three countries to rule the state of Saudi Arabia, but the regime is close to each other extremely. Because the family that ruled the area is a sequential family since its inception till present time, the historical and analytical, descriptive approach is used in this study Based on the points are mentioned above, this study focuses on the following issues, the concept of imamate and succession, its terms and condition, Sheikh Mohammed bin Abdul Wahab, The State of Saudi Arabia in its three stages, The Shahran tribe’s participation in the regime of the Imamate and Succession